Reinventing editorial production in the digital age, in the process of knowledge generation and transfer - Arboleda Sepúlveda, Orlando (2004)
Publishing analyzes in light of the changes proposed by the advances of technology information and communication systems. Impacts of internet points in the production and dissemination of content in environments and organizations, teaching and research. Emphasizes the shared responsibility of library and information science with the publishing industry in the process of information transfer and knowledge creation.